2002
DOI: 10.1016/s1359-6454(02)00158-1
|View full text |Cite
|
Sign up to set email alerts
|

A reaction-layer mechanism for the delayed failure of micron-scale polycrystalline silicon structural films subjected to high-cycle fatigue loading

Abstract: Abstract-A study has been made of high-cycle fatigue in 2-µm thick structural films of n + -type, polycrystalline silicon for MEMS applications. Using an "on-chip" test structure resonating at ~40 kHz, such thin-film polysilicon is shown to display "metal-like" stress-life fatigue behavior in room air environments, with failures occurring after lives in excess of 10 11 cycles at stresses as low as half the fracture strength. Through in-situ monitoring of the natural frequency to evaluate the damage evolution b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
144
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 196 publications
(153 citation statements)
references
References 44 publications
5
144
0
Order By: Relevance
“…Finite-element modeling has shown that a decay in the resonance frequency of the resonators during the test can indicate both cracking as well as oxide formation at the notched cantilever beam. 11 The n + -type polysilicon MUMPs devices were fabricated in run 50 of the process and had a structural film thickness of 2 m and a resonance frequency of approximately 40 kHz. To calibrate the capacitive displacement sensing, this type of device was run in a microvision system 9,18 and in situ under a regular optical microscope.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Finite-element modeling has shown that a decay in the resonance frequency of the resonators during the test can indicate both cracking as well as oxide formation at the notched cantilever beam. 11 The n + -type polysilicon MUMPs devices were fabricated in run 50 of the process and had a structural film thickness of 2 m and a resonance frequency of approximately 40 kHz. To calibrate the capacitive displacement sensing, this type of device was run in a microvision system 9,18 and in situ under a regular optical microscope.…”
Section: Methodsmentioning
confidence: 99%
“…This is because silicon can be microfabricated to produce complex mechanical structures in thin-film form because of highly developed processing methods directly related to semiconductor electronics processing. 1,2 However, silicon is not an ideal structural material: it is quite brittle and subject to several reliability concerns-most importantly, stiction, 3,4 wear, 3,5 and fatigue [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] -that strongly limit the utility of silicon MEMS devices in commercial and defense applications. In particular, premature fatigue failure can occur when devices are subjected to a large number ͑ϳ10 6 -10 12 ͒ of loading cycles at stress amplitudes well below their monotonic fracture stress.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations